Pendampingan Pelaku UMKM Pengrajin Sapu Lidi: Upaya Meningkatkan Kualitas dan Daya Saing Produk di Kelurahan Tembong Kecamatan Cipocok Jaya: Pengabdian - Nadya Bilqis, Aninda; Herdiansyah; Mudaeroh; Putriana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mentoring for Micro, Small, and Medium Enterprises (MSMEs) who are broomstick artisans in Tembong Village, Cipocok Jaya District, was carried out as an effort to improve product quality and expand competitiveness in local and regional markets. This activity was motivated by low product innovation, limited business management knowledge, and minimal marketing strategies used by artisans. The mentoring method was carried out through several stages, namely needs analysis, training to improve production quality, product design and packaging development, business management training, and mentoring on digital-based marketing strategies. The results of the activity showed an increase in artisan skills in producing higher quality broomsticks, more attractive product packaging, and a better understanding of business management and online marketing. This mentoring is expected to increase the competitiveness of MSMEs who are broomstick artisans, open wider market opportunities, and support sustainable local economic development in Tembong Village, Cipocok Jaya District.